Numerical modeling of high current ion beam transport with additional injection of electron beams in drift and accelerating gaps of LIA - Karas, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2016)
The dynamics of a high-current ion beam (HCIB) in the system, consisting of magneto-isolated accelerating gap
and the drift gap (DG) of the experimental model of linear induction accelerator (LIA) has been studied. The optimization
of the magnetic field geometry, the place and time of the additional electron beam injection, as well as its
cross dimension is occurred. It is shown that at found parameters of the beams, the external magnetic field, the injection
of the main and additional electron beams, HCIB can be compensated (HCIB and an additional electron beam
currents practically equal to the initial values and are equal to each other), so that at the exit from the system, ion
beam parameters are suitable for a number important technological applications. Исследована динамика сильноточного ионного пучка (СИП) в системе, состоящей из магнитоизолиро-
ванного ускоряющего зазора и дрейфового промежутка экспериментальной модели линейного индукцион-
ного ускорителя. Проведена оптимизация геометрии магнитного поля, места и времени инжекции дополни-
тельного электронного пучка, а также его поперечного размера. Показано, что при установленных парамет-
рах пучков, внешнего магнитного поля, инжекции основного и дополнительного электронных пучков удаёт-
ся скомпенсировать СИП (токи СИП и дополнительного электронного пучка практически равны первона-
чальным значениям и равны между собой) так, что на выходе из системы его параметры остаются пригод-
ными для ряда важных технологических приложений. Досліджено динаміку сильнострумового іонного пучка (СІП) в системі, що складається з магнітоізольо-
ваного прискорюючого зазору та дрейфового проміжку експериментальної моделі лінійного індукційного
прискорювача. Проведена оптимізація геометрії магнітного поля, місця і часу інжекції додаткового елект-
ронного пучка, а також його поперечного розміру. Показано, що при встановлених параметрах пучків, зов-
нішнього магнітного поля, інжекції основного і додаткового електронних пучків вдається компенсувати СІП
(струми СІП і додаткового електронного пучка практично дорівнюють первинним значенням та є рівними
між собою) так, що на виході з системи його параметри залишаються придатними для ряду важливих техно-
логічних застосувань.